High discharge energy density and ultralow dielectric loss in alkali-free niobate-based glass-ceramics by composition optimization. (December 2022) - Fu, Tongtong; Xie, Shufeng; Liu, Changshuai; Bai, Hairui; Shen, Bo; Zhai, Jiwei
Abstract: The SrO-BaO-Nb2 O5 -SiO2 glass-ceramics with different (Sr, Ba)/Nb ratio were prepared by the melting-crystallized process. With the decrease of (Sr, Ba)/Nb, the bonding species and crystallization activation energy of the glass-ceramics were changed obviously, which caused the change of phase compositions and microstructures on a microscopic scale and the fluctuations of dielectric constant and breakdown strength on a macroscopic scale. Finally, the theoretical energy storage density was up to 18.93 J/cm 3 with a dielectric constant of 84 and breakdown strength of 2256.73 kV/cm. What is more, the dielectric loss was less than 0.004 at room temperature. Furthermore, under the electric field of 640 kV/cm the discharge energy density of the optimal sample (S5) reached 1.14 J/cm 3 which overtopped what has been reported and the discharge time (t0.9 ) was less than 16 ns. Above analysis suggested that the alkali-free niobate-based glass-ceramics have broad application prospects. Graphical Abstract: Image, graphical abstract